The subculture among musicians who perform English popular music in Singapore - Fernandez, Gareth (2015)
As a relatively new and young nation, Singapore has a small but growing arts scene, especially in the original English popular music arena. This paper is primarily concerned with the nature of the subculture among musicians in Singapore who perform English popular music. The study first aims to identify musicians who perform English popular music in Singapore as a subculture, proceeds to examine the nature of this subculture, and finally considers the unique social hierarchical structure within the subcultural group. Seeing as how the number of musicians who perform English popular music was previously too small to even warrant being identified as a subcultural group, this is a particularly interesting topic with little prior research. The study comprises of semi-structured interviews with members of the English popular music subcultural group. This study found that there is indeed a social hierarchy within the subcultural group, where original musicians are of a higher social status than their working musician counterparts.